High quality RNA extraction from Pseudomonas aeruginosa and other bacteria with a novel rapid and cost-effective method - Ivan Stoikov; Ivan Nikolaev Ivanov; Deyan Donchev; Elina Dobreva; Rumyana Hristova; Stefana Sabtcheva (Biotechnology & Biotechnological Equipment)
High-quality mRNA extraction is essential for gene expression assays. In this study, we developed a rapid method (20 min) named FACTS for the extraction of intact RNA from Pseudomonas aeruginosa and compared its performance to established rapid techniques like RNAsnap and CiAR. The RNA integrity, yield, purity and presence of residual genomic DNA were adopted as assessment criteria. Multiple assays for RNA integrity were applied, including the Agilent 2200 TapeStation, QIAxcel capillary electrophoresis, and the newly available Qubit RNA Integrity and Quality (IQ) Assay Kit. The RNA purity and DNA/RNA yield were assessed by spectrophotometry and fluorimetry, respectively. Following Dnase treatment, two-step RT-qPCR for the expression of the rpoD reference gene was performed to evaluate the performance of each method. In terms of RNA integrity, FACTS showed the highest RNA integrity, while in terms of purity, CiAR scored best. RNAsnap resulted in a substantial amount of residual DNA. Pilot experiments for RNA extraction with FACTS from other Gram-negative and Gram-positive bacteria revealed promising results. FACTS is a novel RNA extraction method for rapid highly effective extraction of high-quality RNA from P. aeruginosa and can be used as a cost-efficient alternative to other methods in gene expression studies.